Challenges and Prospects for the Law of Armed Conflict — A Humanitarian Perspective - Wenting Ouyang (Law and Economy, 2024)
The law of armed conflict, as the international legal system that regulates the conduct of war and mitigates its catastrophic consequences, has in recent years faced the challenges of high-tech forms of warfare, the involvement of non-state actors, and the complexities of civil-military integration. To address the complexity of non-international armed conflict, international humanitarian law should be “strategically” disseminated, non-government parties should be urged to issue unilateral declarations or codes of conduct, and the UN Security Council Action Plan model and the Geneva Call’s “Deed of Commitment” model should continue to be explored and implemented. The distinction between combatants and civilians in cyber-armed conflict requires more attention to actual behavior than to the appearance of the operator, with full consideration of the relationship between full membership and function. For the use of autonomous weapons systems, we must balance military interests and the consequences of damage, maximize the recognition and decision-making capabilities of autonomous weapons systems, and maintain human oversight and control during high-risk decisions.